2014
DOI: 10.4028/www.scientific.net/amm.584-586.1355
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Mechanical Properties of Steel and Polypropylene Fiber-Reinforced Concrete

Abstract: The mechanical tests of normal concrete (NC) specimens, steel fiber reinforced concrete (SFRC) specimens and polypropylene fiber reinforced concrete (PPFRC) specimens have been carried out. Fiber-reinforced concretes containing different volume fraction and aspect ratio of steel and polypropylene fibers were compared in terms of compressive, splitting tensile, ultimate tensile properties. Test results indicate that the mechanical properties of NC can be improved by addition of steel fibers and can be enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…As a commonly used composite material for civil construction steel fibre-reinforced concrete (SFRC) combines the positive aspects of both basic materials with respect to its load bearing behaviour (e.g., [ 1 , 2 , 3 , 4 , 5 , 6 ]). Since the plain concrete has excellent resistance to compressive forces but has almost no ability to withstand tensile stresses, the fibre fraction takes up the remaining tensile forces.…”
Section: Introductionmentioning
confidence: 99%
“…As a commonly used composite material for civil construction steel fibre-reinforced concrete (SFRC) combines the positive aspects of both basic materials with respect to its load bearing behaviour (e.g., [ 1 , 2 , 3 , 4 , 5 , 6 ]). Since the plain concrete has excellent resistance to compressive forces but has almost no ability to withstand tensile stresses, the fibre fraction takes up the remaining tensile forces.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported that 1% V f offered better technical benefits than other V f [37]. In addition, the length-to-diameter ratio of fibers (l/d) positively affected the compressive load capacity of SFRC [38]. On the other hand, when V f exceeded a specific threshold, it caused a negative result in the compressive load capacity [39].…”
Section: Introductionmentioning
confidence: 99%
“…It consists of plain concrete (PC) and macroscopic steel fibers, which are mostly produced out of wires (see, e.g., Refs. [1][2][3][4][5][6]. SFRC combines positive features from both of its components and compensates their disadvantages.…”
Section: Introductionmentioning
confidence: 99%